2016
DOI: 10.3926/jotse.155
|View full text |Cite
|
Sign up to set email alerts
|

Post secondary project-based learning in science, technology, engineering and mathematics

Abstract: Project-based learning (PjBL - to distinguish from problem-based learning - PBL) has become a recurrent practice in K-12 classroom environments. As PjBL has become prominent in K-12 classrooms, it has also surfaced in post-secondary institutions. The purpose of this paper is to examine the research that has studied a variety of science, technology, engineering and mathematic subjects using PjBL in post-secondary classrooms. Eleven articles (including qualitative, quantitative and mixed methods) were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 22 publications
0
23
0
8
Order By: Relevance
“…Resultantly, 12 studies were identified that met the inclusion criteria for this study (Table 2). A dearth of the reviewed literature focused on systematic reviews that were specific towards the course or field, such as STEM based degrees (Abramovich et al, 2016;Ralph, 2016). Secondly, researchers Buteau and Muller (2017) demonstrated that technology is key for mathematics courses, specially programming based courses.…”
Section: Technology Use In Postsecondary Mathmentioning
confidence: 99%
“…Resultantly, 12 studies were identified that met the inclusion criteria for this study (Table 2). A dearth of the reviewed literature focused on systematic reviews that were specific towards the course or field, such as STEM based degrees (Abramovich et al, 2016;Ralph, 2016). Secondly, researchers Buteau and Muller (2017) demonstrated that technology is key for mathematics courses, specially programming based courses.…”
Section: Technology Use In Postsecondary Mathmentioning
confidence: 99%
“…These approaches engender increased motivation, increased ability to approach ill‐structured real‐world problems, collaboration, and communication skills (Riegle‐Crumb et al, ; Strobel & van Barneveld, ). They also allow for an interdisciplinary approach through cohesive integration of diverse disciplinary areas (Ralph, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Policy for preschool-aged children focuses on limitations of technology, while there is an increasing emphasis on STEM education and more devices in primary and secondary schools (Thibaut et al, 2018). These policies are slowly having an impact on STEM teacher education in postsecondary institutions (Ralph, 2016). If changes from kindergarten to grade 12 are occurring, changes in ECE should follow.…”
Section: Using Mobile Devices In Ece Stem Educationmentioning
confidence: 99%